Promoting tourism industry in Malacca: Focus on tourist from October 2002 to April 2003 / Siti Rahmaniah Chek - Chek, Siti Rahmaniah (Faculty of Business and Management, 2003)
As we know, Malacca is one of the greatest tourist destinations in the world. It is known as the historical state and has a twin sister city, Chile. This study concentrates on promotional activates that had been done, being done and will be done for the tourism industry in Malacca. The responsibility of all the members in the tourism industry such as agricultural, history & culture, sports, recreation, education, health, food, convention, shopping and promotion sectors will be researched. The data being used in this project paper of "Promoting Tourism Industry in Malacca" is both the secondary and the primary data. For the secondary data, the information was taken from the internal as well as the external sources. Internal data is generated from within the organization in which the research is being done. For example all the data is found in the organization like the Tourism Promotion Department, the Malaysian Airlines System, Equatorial Hotel, Trishaws Organization, Perbadanan Muzium Melaka, Mahkota Parade and etc. All information like the number of tourists or guests is collected and also types of promotion activities practiced in their organization The external data was taken from external sources example the CD-ROM, newspaper cuttings, magazines, journals, brochures, yearly event calendars, pamphlets, articles and World Wide Web. Some of the data was taken from the Public Library of Malacca in Bukit Baru and also from the library of UiTM, Alor Gajah. All the data collected are classified according to the method employed and also the definitions. From the external data, the relevant information is easily collected and it also saves our time rather than to make many interviews for the purpose of collecting all the data associated. The primary data is collected through communication or interviewing, observation and experimentation. The respondents are asked some questions that are relevant to the study. For example, I interviewed the Senior Marketing Manager of Century Mahkota Hotel, Malacca and the Events Manager of Tourism Promotion Department. The personal interview questions include the type of promotional activities that had been done, being done and will be done. Their department mission and future hope is also asked in the personal interview. The observation for this study is made at the places of interest and the yearly events being held. Here, the researcher can see the people's behavior and how they celebrate the events through visiting the historic and fascinating places in Malacca. Are they excited? Surprised? Or regret attending the events and visiting places they attend and go? For example the Ponggal Festival at Gajah Berang which is celebrated by the Chitties on every 15th of January every year. It is a three day festival highlighting the colorful, unique and fascinating traditions, heritage, food and culture of a minority community in Malacca, the Chitties.